Impact of chagas disease in human evolution:the challenges continue - Navarro, Elaine [UNESP]; Pereira, Paulo Camara Marques [UNESP] (Scientific Research Publishing, 2013)
Chagas disease affects 8 to 10 million people worldwide and, although most of them live in Latin America, there has been an increase in cases occurring in countries of Europe and North America although most of them live in Latin America. This study aims to describe the epidemiological situation in the present as well as government and research centers actions, particularly the study group of Chagas disease of the School of Medicine of Botucatu (FMB/UNESP)/Brazil.
Keywords: Congenital transmission; Epidemiology; Vector control; Chagas disease